The Dangers Facing Paramedics While Performing Their Duties - Mohammed Saleh Hussein Zubaid,; Salem Saleh Hussein Zubaid,; Fahd Mohammed Saleh Zubaid,; Nawaf Manea Bouzi Al Duwais,; Mohammed Ali Rashid ALyami,; Al Hassan bin Ahmed Murshid Al Murshid,; Falah Ali Saleh Al-Zubaidi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Paramedics perform important and often life-saving duties on a daily basis. The nature of their role means that they must be able to think quickly and make important decisions about a person's medical condition. Not only is the work that is done by paramedics challenging, but it is also often dangerous. In fact, their occupation is at the highest risk for workplace injuries, musculoskeletal injuries, and illnesses, among other health and safety hazards. In essence, not only are the paramedics subjected to low pay and long hours, but the inherent danger that comes with such a crucial role is not as widely emphasized. Given that we really cannot put a price on the lives of each one of the country's brave paramedics, it is worth learning about the very real threats that these essential healthcare workers face on a regular basis. This paper shall seek to expound upon the greatest dangers that face paramedics while they are performing their duties, and explore in depth some of the most tragic events that have cost the lives of these vital professionals.